2019
DOI: 10.1037/aca0000156
|View full text |Cite
|
Sign up to set email alerts
|

Artists as experts in visual cognition: An update.

Abstract: The question of whether and how visual artists see the world differently than non-artists has long engaged researchers and scholars in the arts, sciences, and humanities. Yet as evidence regarding this issue accumulates, it has become clear that the answers to these questions are by no means straightforward. With a view to advancing ongoing debate in this field, the current study aimed to replicate and extend previous research by exploring the differences in visual-spatial ability between art students (n = 42)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 72 publications
(154 reference statements)
8
62
0
4
Order By: Relevance
“…In contrast, the art students in the current study already had amassed several years of artistic experience and had gained entry to a prestigious art and design school. As our prior study demonstrated (Chamberlain et al 2019), these students were already outperforming non-art students prior to starting their foundation course. Therefore, it is possible that the ATTA may not have been sensitive enough to measure changes in artistic creative output over time in an expert group.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In contrast, the art students in the current study already had amassed several years of artistic experience and had gained entry to a prestigious art and design school. As our prior study demonstrated (Chamberlain et al 2019), these students were already outperforming non-art students prior to starting their foundation course. Therefore, it is possible that the ATTA may not have been sensitive enough to measure changes in artistic creative output over time in an expert group.…”
Section: Discussionmentioning
confidence: 70%
“…A recent extension of this work is a more comprehensive study by Chamberlain et a. (2019), examining artists' and non-artists' performance on a wide range of perception and drawing tasks, and largely replicating this basic finding (see also Kozbelt & Seeley, 2007).…”
Section: Whilst Research Bymentioning
confidence: 64%
See 1 more Smart Citation
“…Recognition of out-of-focus pictures. The Out-of-Focus Pictures Task, similar to that used by Kozbelt (2001) and recently used by Chamberlain et al (2019), assesses the ability to go beyond the information given to identify the object represented in the image. Because this task requires going beyond the information given, we suggest that this task requires filling in what one can see with visual imagery.…”
Section: Visual Imagery Measuresmentioning
confidence: 99%
“…Raters coded the open-ended responses using a key of correct responses developed by Chamberlain et al (2019). Raters practiced coding using responses from the Chamberlain study, and once 80% agreement was achieved on the practice responses, they coded responses from this study.…”
Section: Visual Imagery Measuresmentioning
confidence: 99%